Materializing through the Skylight - Wayne Michael Charney (Oz, 1998)
Whether or not any structure built for a world's fair can ever hope to aspire to any sort of enduring architectural significance that extends well beyond the short life span of the exposition for which it was built is a question that has already been much debated and perhaps settled in the affirmative especially for some of the more visually exciting and experimental contemporary exhibition pavilions.